2021
DOI: 10.1115/1.4050539
|View full text |Cite
|
Sign up to set email alerts
|

Non-Newtonian Blood Modeling in Intracranial Aneurysm Hemodynamics: Impact on the Wall Shear Stress and Oscillatory Shear Index Metrics for Ruptured and Unruptured Cases

Abstract: When simulating blood flow in intracranial aneurysms, the Newtonian model seems to be ubiquitous. However, analyzing the results from the few studies on this subject, the doubt remains on whether it is necessary to use non-Newtonian models in wall shear stress (WSS) simulations of cerebral vascular flows. Another open question related to this topic is whether different rheology models would influence the flow parameters for ruptured and unruptured cases, especially because ruptured aneurysms normally have morp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 41 publications
2
13
0
Order By: Relevance
“…The commonly used viscosity values for the Newtonian model may vary by 10% among different patient groups ( Valen-Sendstad et al, 2018 ). The effects of different blood rheological models on hemodynamics have been evaluated in stenotic carotid ( Mendieta et al, 2020 ) and coronary ( Abbasian et al, 2020 ) arteries and intracranial aneurysms ( Oliveira et al, 2021 ). It has been found that the effects of different blood rheology models on simulation results depend on the specific hemodynamic parameters, and the difference in hemodynamic parameters can be more than 50% compared to the Newtonian model.…”
Section: Verification Validation and Uncertainty Quantificationmentioning
confidence: 99%
“…The commonly used viscosity values for the Newtonian model may vary by 10% among different patient groups ( Valen-Sendstad et al, 2018 ). The effects of different blood rheological models on hemodynamics have been evaluated in stenotic carotid ( Mendieta et al, 2020 ) and coronary ( Abbasian et al, 2020 ) arteries and intracranial aneurysms ( Oliveira et al, 2021 ). It has been found that the effects of different blood rheology models on simulation results depend on the specific hemodynamic parameters, and the difference in hemodynamic parameters can be more than 50% compared to the Newtonian model.…”
Section: Verification Validation and Uncertainty Quantificationmentioning
confidence: 99%
“…If the fittings for both models are near to their respective statistical function error analyses, the Cross model, which has lower parameters, should be selected as a rule of thumb. The Carreau-Yasuda model has found application in some biological systems, for instance in the modelling of the non-Newtonian blood flow in intracranial aneurysm cases, where the normality of the residuals has been checked with several normality models [4].…”
Section: ( )mentioning
confidence: 99%
“…Many fluids on are non-Newtonian and, as a result, rely on their viscosity to function properly. The method by which non-Newtonian rheological data is measured, corrected, and analyzed is critical in the process of formulating new materials and processes [1][2][3][4]. When a fluid does not comply with Newton's law of viscosity, it is said to be non-Newtonian.…”
Section: Introductionmentioning
confidence: 99%
“…ntracranial saccular aneurysms represent an enigmatic pathology with potential for severe and complex clinical consequences in the event of rupture and aneurysmal subarachnoid hemorrhage (aSAH). [1][2][3][4][5][6][7][8][9][10][11] Despite enquiry, standardized algorithms to predict odds of rupture in individual lesions remain under investigation. [1][2][3][4][5][6][7][8][9][10][11] Nevertheless, advances in noninvasive imaging techniques, studies in computational flow dynamics, and expanding applications of translational basic science have identified potential risk factors.…”
mentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11] Nevertheless, advances in noninvasive imaging techniques, studies in computational flow dynamics, and expanding applications of translational basic science have identified potential risk factors. [1][2][3][4][5][6][7][8][9][10][11] Particular interest in recent studies has focused on hemodynamic stress, aneurysm wall inflammatory pathways, aneurysm dome morphology, and high-resolution vessel wall imaging (HR-VWI). [1][2][3][4][5][6][7][8][9][10][11] The clinical application of such studies has centered on the identification of so-called "high-risk lesions," in hopes that prophylactic treatment of unruptured intracranial aneurysms (IAs) may decrease rates of aSAH and thus increase the proportion of patients who achieve good outcome.…”
mentioning
confidence: 99%